(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Islam MA, Idris MH, Bhuiyan MKA, Ali MS, Abdullah MT, Kamal AHM. 2022. Floristic diversity, structure, and carbon stock of mangroves in a tropical lagoon ecosystem at Setiu, Malaysia. Biodiversitas 23: 3685-3697. Mangroves in lagoon habitats play an important role in ecosystem functions. Many studies on mangrove habitats are available in coastal habitats, however, the information on the lagoon ecosystems in tropical climates is scanty, especially regarding its vegetation and carbon storage. This study was carried out to assess the status of species diversity, composition, zonal structure and carbon storage of mangrove vegetation in Setiu lagoon, Malaysia. We used the transect line plots method in representative landward and small fringe island areas. The results showed that the floristic diversity of mangroves comprised 18 true mangroves and 11 associates, of which Avicennia rumphiana and Ceriops decandra were listed as threatened by IUCN. The stem density and basal area ranged from 1533 to 3800 individuals. ha-1 and 18.98-37.97 m2 ha-1, respectively. The mean tree diameter was 9.80 ± 2.85 cm, with a tree height of 10.35 ± 2.14 m. The mangrove species with the highest importance value index (IVI) was Rhizophora mucronata with 134.86, while the lowest was Acanthus ebracteatus with 13.23. The study revealed that small fringe islands in the lagoon were more diverse with biodiversity index values always higher than the landward zone. Total biomass from the dominant mangrove species was estimated at 522.9 t ha-1 with estimated carbon storage of 261.45 t ha-1 and sequestration potential of 959.54 t CO2 ha-1. Compared to the other mangrove ecosystems elsewhere, this study recommends that the Setiu lagoon is considered to be a healthy and newly generated mangrove forest. Therefore, proper monitoring is needed to ensure mangrove ecosystem health and functions.